2015
DOI: 10.1007/s10072-015-2265-3
|View full text |Cite
|
Sign up to set email alerts
|

Workers with disability: the case of multiple sclerosis

Abstract: The impact of the multiple sclerosis (MS) on the individual's ability to work is important especially because the onset of the disease occurs mainly between 20 and 30 years of age. This study evaluated different factors associated with job maintenance using a questionnaire that defined what factors are considered obstacle or help in work management. A cross-sectional study of people with MS was carried out in Italy. A total of 1016 individuals with MS were enrolled in the study. Our results showed that negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Work beliefs and attitudes are also critical in maintaining employment following a diagnosis of MS. In a cross-sectional study of 1016 individuals, a negative attitude from colleagues was associated with lower odds of being employed (Ponzio et al, 2015). Similarly, Honan et al (2012, 2014) reported a moderate association between non-supportive workplace and reduction in work hours, although their community sample perceived MS-related mobility and movement difficulties to be more problematic in the workplace than disease-specific cognitive and psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Work beliefs and attitudes are also critical in maintaining employment following a diagnosis of MS. In a cross-sectional study of 1016 individuals, a negative attitude from colleagues was associated with lower odds of being employed (Ponzio et al, 2015). Similarly, Honan et al (2012, 2014) reported a moderate association between non-supportive workplace and reduction in work hours, although their community sample perceived MS-related mobility and movement difficulties to be more problematic in the workplace than disease-specific cognitive and psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although the lifespan of MS patients has been extended in the past few decades [ 22 , 23 ], the proportion dropping out of the workforce has not decreased [ 24 , 25 ], and fewer than half of patients maintain full- or part-time employment [ 26 ], suggesting a gap in awareness of the burdens on patients with MS as they age into their 40s and 50s. Furthermore, patients entering middle age are met with unique challenges compared with those of younger patients, including increased prevalence of physical comorbidities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, we consider it appropriate to suggest OPs to encourage MS workers to discuss their disease even at workplace by using the most appropriate stakeholders (i.e. OPs, Human Resource managers and/or employers) since, the available literature data demonstrated that the disclosure of the disease is positively correlated to preserving job33 ) , whereas on the contrary the lack of disclosure could complicate the workplace conditions and/or may create hostile or difficult relationships with colleagues28, 34 ) . In this context, the OPs can play a central role in evaluating and identifying the most suitable accommodations to be taken by employers for MS workers, in suggesting vocational interventions to adequately manage the different and complicated aspects of the disease in the workplace and in supporting MS workers, co-workers and employers with specific and targeted counselling programs and strategies10, 28, 32, 35 ) .…”
Section: Discussionmentioning
confidence: 99%